TAXES AND ECONOMIC INEQUALITY: AN ANALYSIS FROM THE PERSPECTIVE OF VARIOUS STUDIES - Andi Andi (INTERNATIONAL JOURNAL OF SOCIETY REVIEWS, 2026)
Taxes play an important role in reducing economic inequality by redistributing income and increasing access to public services. Progressive tax systems, which focus on higher incomes, have been proven effective in reducing economic inequality. Studies reveal that funds collected from progressive taxes can be used to fund social programs such as education, health, and social assistance, all of which contribute to improving the welfare of vulnerable groups. However, the effectiveness of tax policy in reducing inequality largely depends on its proper design and implementation. Poorly designed taxes, such as flat consumption taxes, can be detrimental and increase the economic burden on low-income groups. Therefore, it is important to design fair and progressive tax policies and implement effective systems to ensure compliance and fairness in tax collection. Furthermore, various studies emphasize that tax policy alone is not sufficient to reduce economic inequality. Tax interventions need to be supported by other economic and social policies, such as fair minimum wage policies, inclusive education, and adequate social protection. This combination of policies creates a more inclusive and equitable ecosystem, where every individual has equal opportunities to improve their welfare. Overall, tax is an important tool in addressing economic inequality, but it requires a multi-layered and collaborative approach between various policies. Reforms in the tax system need to be aligned with policies on resource redistribution and improving access to essential public services to support the creation of a more equitable and inclusive society.